The adventures of Sherlock Holmes and the memoirs of Sherlock Holmes - Doyle, Arthur Conan, 1859-1930 (Penguin classics., 2001)
Presents over twenty mystery stories featuring popular detective Sherlock Holmes and his devoted sidekick Dr. Watson.